2012
DOI: 10.1111/j.1095-8649.2012.03261.x
|View full text |Cite
|
Sign up to set email alerts
|

Pacific sleeper shark Somniosus pacificus trophic ecology in the eastern North Pacific Ocean inferred from nitrogen and carbon stable‐isotope ratios and diet

Abstract: Stable-isotope ratios of nitrogen (δ¹⁵N) and lipid-normalized carbon (δ¹³C') were used to examine geographic and ontogenetic variability in the trophic ecology of a high latitude benthopelagic elasmobranch, the Pacific sleeper shark Somniosus pacificus. Mean muscle tissue δ¹³C' values of S. pacificus differed significantly among geographic regions of the eastern North Pacific Ocean. Linear models identified significant ontogenetic and geographic variability in muscle tissue δ¹⁵N values of S. pacificus. The tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 105 publications
0
7
0
Order By: Relevance
“…They suggested that the diet of the Pacific sleeper shark probably also varies by time and location of capture and in response to prey availability. Therefore, given the evidence of ontogenetic, seasonal, and geographic diet shifts in many shark species, including the Greenland shark, southern sleeper shark, and Pacific sleeper shark (Orlov and Moiseev, 1999;Fisk et al, 2002;Yano et al, 2007;Courtney and Foy, 2012), the absence of sea lion tissue in the sampled sharks is, perhaps, not surprising and does not contradict our indirect evidence of predation on Steller sea lions.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…They suggested that the diet of the Pacific sleeper shark probably also varies by time and location of capture and in response to prey availability. Therefore, given the evidence of ontogenetic, seasonal, and geographic diet shifts in many shark species, including the Greenland shark, southern sleeper shark, and Pacific sleeper shark (Orlov and Moiseev, 1999;Fisk et al, 2002;Yano et al, 2007;Courtney and Foy, 2012), the absence of sea lion tissue in the sampled sharks is, perhaps, not surprising and does not contradict our indirect evidence of predation on Steller sea lions.…”
Section: Discussionmentioning
confidence: 93%
“…This size bias could be driven by the possible absence of larger sharks in the region or by the possible size bias of long-lining toward younger, smaller individuals (for remarks on landing and sampling likelihood for long-line gear, see Orlov and Moiseev, 1999;Yano et al, 2007;Courtney and Sigler, 2007). Courtney and Foy (2012) reported an increase in trophic position with TL in Pacific sleeper sharks. They suggested that the diet of the Pacific sleeper shark probably also varies by time and location of capture and in response to prey availability.…”
Section: Discussionmentioning
confidence: 99%
“…Despite increasing abundance of the species in Russian and American waters registered in recent years (Wright and Hulbert, 2000;Borets et al, 2001;Glebov et al, 2003;Starovoitov et al, 2004;Courtney and Sigler, 2007), the data on spatial distribution of the shark are fragmentary, and they are restricted to the western Bering Sea and Kuril and Kamchatka waters of the Pacific Ocean. In addition, the materials on the biology of the species are fragmentary and not numer ous (Bright, 1959;Anderson et al, 1979;Tanaka et al, 1982;Ebert et al, 1987;Orlov, 1999;Orlov and Moi seev, 1999;Yang and Page, 1999;Glubokov, 2004;Shaufler et al, 2005;Chuchukalo, 2006;Hulbert et al, 2006;Sigler et al, 2006;Yano et al, 2007;Wischniowski, 2008;Courtney and Foy, 2012). The maps of spatial distribution of Pacific sleeper shark in the western Bering Sea have been published recently (Atlas…, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is essential to consider the geographic influence on diet since bacterial composition likely also varies accordingly [35]–[38]. The impact of geography on oral bacteria and resistance is still uncertain but one study [12] reported that nurse sharks caught in Belize and the Florida Keys exhibited a similar antibiotic resistance pattern from cloaca-anal swabs, but a seemingly higher bacterial count per sample was seen in the nurse sharks caught in the Florida Keys.…”
Section: Discussionmentioning
confidence: 99%